Pengaruh Penggunaan Smartphone Terhadap Hasil Belajar Siswa - Ningsih, Sulistio; Yanti, Syafridha; Wahyuni, Sri (Jumper: Journal of Educational Multidisciplinary Research, 2023)
This study aims (1) to find out how students use smartphones at SMA Negeri 2 Takengon (2) to find out whether smartphone use affects student learning outcomes. The results of this study are that the value of Y = 0.25 + 0.-12 where the value of the coefficient b = -0.12 (negative) then the regression model is negative or unidirectional, meaning that if smartphone use increases, student scores will decrease. the results of the correlation analysis to find out how closely the X and Y variables are related, the value of r = 0.9915 shows that there is a very strong relationship between the X and Y variables, namely Smartphone Use and Student Learning Outcomes and to determine the magnitude of the influence of smartphone use on outcomes student learning can be seen from the degree of determinant (coefficient of determination), r2 as follows r2 = 89% which shows that student learning outcomes are influenced by smartphone use by 89%.